Challenges on Malaysian teachers’s self efficacy in online teaching during COVID-19 - Abdul Rashid, Khadijah Khalilah; Che Haron, Sueraya; Che Haron, Sabrina (Human Resource Management Academic Research Society, 2021)
Realizing online lessons during COVID-19 needs huge participation from both teachers and students. It is not easy to maintain teachers’ performance in this unusual time. There are many challenges faced by teachers in online teaching during this pandemic. This study reviews literature to find out Malaysian teachers’ self-efficacy related to their performance in online teaching based on Bandura’s four main sources of self-efficacy. This study has its importance in revealing true challenges experienced by the teachers to deliver online lesson especially in Malaysia. This is a descriptive study that is enriched with literature on Malaysian teachers’ challenges in online teaching from different published resources from the past two years such as journal articles, newspapers and online essays. The results show that the challenges related to self-efficacy faced by Malaysian teachers are their unreadiness in conducting online teaching, low motivation caused by various problems, pressure in balancing teaching duty and household chores, and worrying about the adoption and acceptance of students for online learning. These challenges were categorized based on sources of self-efficacy, that consists of mastery teaching experience, vicarious experience, social persuasion and physiological and emotional behaviours. It is concluded that the most effective way to obtain high self-efficacy level is through mastery experiences. This study proposes further research on solutions for the challenges related to teachers’ self-efficacy by implementing Bandura’s four main sources of efficacy beliefs.